Advanced Driver Assistance System Integration with Electronic Toll Collection: Seamless Payment Processing for Autonomous and Connected Vehicles - Sarath Babu Gosipathala (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This paper presents an advanced integration framework between Advanced Driver Assistance Systems (ADAS) and Electronic Toll Collection (ETC) that enables seamless, high-speed payment processing for autonomous (AVs) and connected vehicles (CVs). The proposed Autonomous Vehicle Toll Integration System (AVTIS) directly addresses the technical and regulatory challenges of next-generation transportation, where transactions must be entirely automatic, secure, and instantaneous at full highway speeds. Our methodology establishes secure, dedicated communication protocols between vehicle onboard units, roadside infrastructure, and a decentralized payment network. Crucially, AVTIS employs a hybrid blockchain architecture—leveraging Directed Acyclic Graph (DAG) technology for high throughput—to ensure secure, pseudonymous vehicle authentication and non-repudiable payment authorization while strictly maintaining user privacy. We introduce a novel, state-aware V2I communication protocol specifically designed to guarantee transaction finality within the brief communication window available at high speeds. The framework supports diverse payment mechanisms, including cryptocurrency and digital wallets, and features advanced security measures against spoofing and denial-of-service (DoS) attacks. Experimental validation using both simulation and a limited real-world deployment demonstrates exceptional transaction success rates and complete integration capability with existing ETC systems, marking a critical step toward fully automated mobility-as-a-service (MaaS) ecosystems.